Determinan Harga Saham pada Perusahaan Pertambangan Di Indonesia - Tarisa Aurella; Elok Heniwati; Ira Grania Mustika (DINASTI RESEARCH, 2024)
Before making an investment, investors must analyze stock prices to avoid unfavorable situations. This study aims to determine the effect of Return on Asset (ROA), Return on Equity (ROE) and Current Ratio (CR) on stock prices in mining companies listed on the Indonesia Stock Exchange. This study uses quantitative research. The population in this study is mining companies listed on the Indonesia Stock Exchange. The sample selection used purposive sampling and obtained 42 data samples. The data in this study are secondary data obtained from the Indonesia Stock Exchange (IDX) and the company's official website. This study uses data analysis techniques, namely multiple linear regression analysis using IBM SPSS version 29. The results of this study indicate that return on assets does not affect stock prices in mining companies, return on equity has a positive and significant effect on stock prices in mining companies and current ratio does not affect stock prices in mining companies.